Outbreak of porcine epidemic diarrhoea virus (PEDV) in Abruzzi region, central‐Italy. Issue 2 (18th December 2017) - Pizzurro, Federica; Cito, Francesca; Zaccaria, Guendalina; Spedicato, Massimo; Cerella, Angelo; Orsini, Massimiliano; Forzan, Mario; D'Alterio, Nicola; Lorusso, Alessio; Marcacci, Maurilia
Abstract: Here we report and characterize a porcine epidemic diarrhea (PED) outbreak which occurred in a swine fattening farm in the province of Teramo, Abruzzi region (central Italy), in January 2016. PED virus (PEDV) identification was determined by real‐time RT‐PCR performed on RNAs purified from fecal samples collected from two symptomatic pigs. Whole genome sequence (PEDV 1842/2016) was also obtained by next generation sequencing straight from RNA purified from one fecal sample. Genome comparison with extant global PEDV strains revealed a high nucleotide identity with recently reported European and American S‐INDEL PEDVs. Efficient sequencing, share of genomic data combined with the implementation of epidemiological tools would be the ideal approach for study and analysis of transboundary infectious diseases as PED. Abstract : A porcine epidemic diarrhoea (PED) outbreak occurred in a swine fattening farm in Teramo province, Abruzzi region, in January 2016.Whole genome of the occurring PEDV was obtained straight from RNA purified from infected faeces. Genome comparison with extant global PEDV strains revealed a high nucleotide identity with recently reported European and American S‐INDEL PEDVs.